Ekologisten ja kolonisaatiokriittisten äänten kohtaamisia.: Näkökulmia luontosuhteen kuvaukseen Nils-Aslak Valkeapään runoudessa - Kovář, Michal (AVAIN - Kirjallisuudentutkimuksen aikakauslehti, 2015)
Encounters of Ecological and Postcolonial Voices. Perspectives to Human-Nature Relations in Nils-Aslak Valkeapää’s Poetry This article examines the encounters of environmental and decolonial voices in Sámi national writer, Nils-Aslak Valkeapää’s (1943–2001) poetry, focusing on his three main works: Ruoktu váimmus (1985, Trekways of the Wind 1994), Beaivi, Áhčážan (1988, The Sun, my Father 1997) and Eanni, Eannážan (2001, ”Earth, my Mother”). The interest lies in the manifold and occasionally contradictory manners in which Valkeapää describes the human relation with nature. According to my observations, his poems reflect harmonious coexistence of man and nature, but in addition to that, parallelism of various overlapping dimensions is also present. The close interaction between man and nature in Valkeapää’s poems has also been the subject of earlier research interest (e.g. Dana 2003 and Valkeapää 2011). In this article, a new perspective is applied by examining the representation of human-nature relations as a meeting place of ecological and decolonial themes. The theoretical framework of this article comes mainly from theoretical trends called postcolonial ecocriticism and indigenous methodologies, interdisciplinary, decolonially oriented approaches used globally by researchers with native background.